Інформаційне забезпечення соціальної реклами: проблеми та перспективи - Назар, Токар; Мина, Жанна (Видавництво Львівської політехніки, 2020)
This article describes social advertising as an important phenomenon in society that raises current issues. You can also see foreign experience in this area and assess the main problems in Ukraine.
Keywords: неурядова організація; соціальна реклама; модель; ЗМІ; тренінг; інформація